Aplikasi Pendeteksi Dini Penyakit Hepatitis Menggunakan Mesin Inferensi Forward Chaining Berbasis Android - Bambang Agus Herlambang; Aditya Galih Prathama; Rahmat Robi Waliyansyah (Universitas Islam Sultan Agung, 2021)
The development of the world of information technology or commonly known as IT is indeed extraordinary rapid that is in harmony with human needs one of which is helping medical staff to analyze the disease one of which is Hepatitis. Hepatitis is inflammation that occurs in the human liver and its types are Hepatitis A, Hepatitis B and Hepatitis C. Application is a program developed to carry out certain functions for certain users who aim to achieve certain goals. On this occasion the authors developed the Hepatitis Disease Early Detection Application Using an Android-Based Forward Chaining Inference Machine to display the classification of Hepatitis A, Hepatitis B or Hepatitis C. The results obtained in this study are the Early Detection Application of Hepatitis Using the Android-Based Forward Chaining Inference Machine successfully designed to provide support in the form of convenience for doctors regarding the description of hepatitis that is Hepatitis A, Hepatitis B and Hepatitis C and tested using Black Box testing with the results are feasible to use, the White Box test with the results of edges, nodes, predicate nodes and independent pathways is 22 and UAT testing with 92% results from 5 respondents.